An introduction to the history of psychology - Hergenhahn, B. R. 1934-2007 (Wadsworth, Cencage Learning, 2014)
Demonstrates most of the concerns of contemporary psychologists are manifestations of themes that have been part of psychology for hundreds - or even thousands-of years. This book features numerous photographs and pedagogical devices, along with its biographical material on key figures in psychology